Middle/Late Bronze Age plant communities and their exploitation in the Cávado basin (NW Portugal) as shown by charcoal analysis : the significance and co-occurrence of Quercus (deciduous) : fabaceae - Figueiral, Isabel (2004)
Plant communities and their possible exploitation during Late Prehistory are studied based on charcoal data from four archaeological sites. Settlement location in the area appears to have been chosen on the basis of easy access to rivers and good arable land. Querens (deciduous) and Fabaceae appear to have been the main source of wood; this is in agreement with previous data from north-western Portugal. The abundance of Fabaceae, which thrive in open well-lit areas, is seen as a direct consequence of woodland clearance. The co-occurrence of Quercus (deciduous) and Fabaceac appears as a distinctive feature in north-western Portugal during Late Prehistory and Protohistory. Fabaceae have remained a familiar component of the vegetation cover ever since. Pinus pinaster is present as isolat ed individuals, in contrast to its present-day abundance.